Association between nutritional, inflammatory and oxidative status (NIOS) and risk of adverse outcomes in patients on haemodialysis (HD): the NIOS-HD prospective cohort study protocol. Issue 9 (20th September 2022) - Foshati, Sahar; Askari, Gholamreza; Bagherniya, Mohammad; Mortazavi, Mojgan; Moeinzadeh, Firouzeh; Taheri, Shahram; Heidari, Zahra; Rouhani, Mohammad Hossein
Abstract : Introduction: The mortality of patients on chronic haemodialysis is 10–30 times greater than that of the general population and over 60% of these individuals die within the first 5 years of beginning haemodialysis. Although causes for excessive mortality in haemodialysis patients are not clearly defined, it seems that nutrition, inflammation and oxidative stress play key roles in this regard. Until now, no cohort study has focused on the association between nutritional, inflammatory or oxidative status and risk of complications and adverse outcomes in Iranian haemodialysis patients. Therefore, we sought to fill this gap and designed the Nutritional, Inflammatory, and Oxidative Status in Hemodialysis (NIOS-HD) prospective cohort study to determine the association of dietary factors, malnutrition, anthropometric indices, body composition, inflammation and oxidative stress with quality of life, dialysis access infections, hospitalisation, potential years of life lost and mortality in adults on maintenance haemodialysis in Isfahan, Iran. Methods and analysis: The sample size of this cohort was estimated to be 300 participants. At baseline, demographic, medical and dialysis-related data of eligible patients will be recorded. In addition, participants will undergo anthropometric measurements, malnutrition assessment and body composition analysis. Also, their dietary intake and quality of life will be evaluated through interviewer-administered questionnaires. Moreover, their fasting blood samples will be collected and stored for biochemical assays including transthyretin, albumin, serum amyloid A, pentraxin-3, trimethylamine N-oxide, myeloperoxidase, paraoxonase-1 and superoxide dismutase. After baseline evaluation, patients will be followed up to 3 years to update exposure information (except biochemical assays) and measure adverse outcomes. Finally, collected data will be analysed using descriptive and inferential statistics. Ethics and dissemination: The NIOS-HD is in agreement with the Declaration of Helsinki and has been approved by the Ethics Committee of Isfahan University of Medical Sciences (reference number: IR.MUI.RESEARCH.REC.1399.605). Findings of this study will be published in academic journals.